Results of Treatment of the GEU at the Infundibulum of Fallopian Tube by Endoscopic Surgery at National Hospital of Obstetrics and Gynecology - Van Du, Vu; Ngoc Quyen, Nguyen; Duong Truyen, Nguyen; Dang Tuan, Mac (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 3, 2022)
Abstract: Objective: To evaluate the results of laparoscopic management of tubal cystectomy at the National Hospital of Obstetrics and Gynecology. Subjects and research methods: A retrospective descriptive study of medical records of patients with tubal cystectomy at the National Hospital of Obstetrics and Gynecology from November 1, 2020, to the end of December 31, 2020. Results: The most common age group for tubal pregnancy is 25-34 years old (59.1%), and the least common is under 20 years old (1.1%). 57% of patients had less than two children. The size of the gestational mass at surgery ≤ 3cm accounted for the highest percentage (86%), and the group of patients with gestational mass ≥ 5cm accounted for only 1.1%. Morphology of the gestational mass before surgery: most of the gestational masses were unbroken, accounting for 69.9%, and 5.9% had ruptured gestational masses. Mainly during surgery, the amount of blood in the abdomen is from 100-500 ml (54.8%), and blood volume >500 ml only accounts for 8.1%. There were 7.5% of patients who had laparoscopic tubal conservation, and the remaining 92.5% had a laparoscopic tubal resection. The group of patients who had never had children and had only one child had the highest rate of tubal preservation, in which the rate of tubal preservation in the group of patients without children was up to 17.6%. Total treatment time after laparoscopic surgery is usually less than 4 days, an average of 2.6±1.2 days. Out of 186 patients studied, only one patient required a blood transfusion. There were no cases of complications after laparoscopic surgery. Conclusions: The most common age group to get pregnant is women of reproductive age. Most of the patients come to the hospital in the early stage, the pregnancy mass has not broken, and the size is small. Patients without children had the highest rate of tubal preservation. The proportion of patients requiring blood transfusion was not significant, and there were no cases of complications after laparoscopic surgery. Keywords: results of treatment, GEU at the infundibulum of fallopian tube, endoscopic surgery.